Variability in measuring physical activity in children with cerebral palsy - Mitchell, L.; Ziviani, J.; Boyd, Roslyn (2015)
Copyright © 2014 by the American College of Sports Medicine. Introduction: This study aimed to establish the variability in the measurement of habitual physical activity using the ActiGraph® GT3X+ accelerometer in children with cerebral palsy (CP). Method: Repeated measures: Independently ambulant children with unilateral CP (n = 30; age, 11 yr 3 months (2 yr 4 months)) completed standardized tasks over two consecutive days, wearing an ActiGraph® GT3X+ accelerometer and HR monitor. Testing protocol comprised 5 min of seated rest (REST), walking at light, moderate, and vigorous pace, and rapid stepping on/off a step. Agreement was calculated between days using intraclass correlation coefficients (ICC) (two-factor mixed agreement model). Minimum detectable difference was calculated (minimum detectable difference = [SDv1 - ICC] × 1.96v2). Performance variability: Participants (n = 102) wore an ActiGraph® GT3X+ accelerometer for 4 d in the community. Activity counts were converted into activity intensity using uniaxial-derived cut points to classify the time spent in moderate-to-vigorous physical activity (MVPA). Between-day intraclass reliability coefficients (R) and Spearman-Brown prophecy formula ([ICCdesired/(1 - ICCdesired)][(1 - ICCestimated)]/ICCestimated]) were calculated. Results: Agreement between repeated measures was strong for light physical activity and MVPA (ICC, 0.80). For MVPA, the minimum detectable difference was 1412 counts per minute. In the community, 345 d (87%) were recorded. Three days of monitoring produced acceptable variability estimates of MVPA (R = 0.63-0.73). Spearman-Brown prophecy analysis estimated that 3 d would achieve a reliability coefficient of 0.7 and 11d would achieve 0.9. Conclusions: Measurement of habitual physical activity using the ActiGraph® GT3X+ accelerometer is reliable under controlled walking and stepping conditions as well as in a community environment in independently ambulant children and adolescents with CP.